2017
DOI: 10.5194/acp-17-1865-2017
|View full text |Cite
|
Sign up to set email alerts
|

Lidar detection of high concentrations of ozone and aerosol transported from northeastern Asia over Saga, Japan

Abstract: Abstract. To validate products of the Greenhouse gases Observing SATellite (GOSAT), we observed vertical profiles of aerosols, thin cirrus clouds, and tropospheric ozone with a mobile-lidar system that consisted of a two-wavelength (532 and 1064 nm) polarization lidar and a tropospheric ozone differential absorption lidar (DIAL). We used these lidars to make continuous measurements over Saga (33.24 • N, 130.29 • E) during 20-31 March 2015. High ozone and high aerosol concentrations were observed almost simul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…inaccuracies in the CTM simulations. The emission inventory used within FARM likely underestimates the real emissions, as also reported in other cases, and for different models, in the scientific literature (e.g., EMEP, 2016;Uchino et al, 2017). In particular, the boundary conditions could not be accurate enough for our aims owing to the abrupt change of the national emission inventory grid resolution (12 km) to the local scale (1 km).…”
Section: Model-measurement Discrepanciesmentioning
confidence: 84%
“…inaccuracies in the CTM simulations. The emission inventory used within FARM likely underestimates the real emissions, as also reported in other cases, and for different models, in the scientific literature (e.g., EMEP, 2016;Uchino et al, 2017). In particular, the boundary conditions could not be accurate enough for our aims owing to the abrupt change of the national emission inventory grid resolution (12 km) to the local scale (1 km).…”
Section: Model-measurement Discrepanciesmentioning
confidence: 84%
“…The depolarization signals we measured may have been closer to those reported by Heese et al [54], i.e., a mix of particles from biomass and industrial burning. Also, following an analysis from Uchino et al [44], the main aerosol component we detected in this period might have been sub-micrometer-sized spherical particles, because the depolarization signal was small and the backscatter-related Ångström exponent is on the order of 1-2 ( Figure 5, middle panel).…”
Section: Discussionmentioning
confidence: 59%
“…The integrated backscattering coefficients (IBCs) of stratospheric aerosols from the tropopause level to 33 km were 6.81 × 10 −5 sr and 7.58 × 10 −5 sr on 26 January and 28 February, respectively. From here, we determined the stratospheric AOD by assuming that the LiDAR ratio for stratospheric aerosols is 50 sr −1 [44]. This yields stratospheric AODs of 0.0034 on 26 January and 0.0038 on 28 February 2017.…”
Section: Lidar Resultsmentioning
confidence: 99%
“…Analysis of multiple AERONET sites in East Asia during the 2001-2010 period showed that the area is dominated by mineral dust during spring months, likely transported from the Gobi and Taklamakan Deserts (Eck et al, 2005;Huang et al, 2008;Logan et al, 2013). The dominance of these outflowing aerosols continues to be observed as far away as Japan (Ikeda et al, 2014;Uchino et al, 2017). shows certain similarity, but is higher in general.…”
Section: Case Studymentioning
confidence: 99%